(untitled) (ModaPalavra e-periódico, 2020)
This article aims to investigate and experiment environmentally sustainable solutions using cotton knit waste and hand knitting to develop new fashion products. The know waste came from imperfect knit fabrics discarded by fabric industries and circular knit garments discarded by consumers. The tool used as a creative mean of development was the morphological chart, which allowed approximately one hundred and fifty ideas of garments to be generated. Five ideas were identified as main product concept. A prototype of a vest was made to test the viability of the use of the morphological chart do develop a creative fashion product. The reproducibility of the methodology was successfully tested by handcraft artists that work with handknitting